An investigation of the use of SCUBE1 protein as an early prognostic marker in predicting prognosis after cardiopulmonary resuscitation in cardiac arrest patients (Annals of Medical Research, 2021)
Aim: To evaluate the usefulness of Signal Peptide-CUB-EGF Domain-Containing Protein-1 (SCUBE1) protein as an early prognostic marker in predicting survival, resuscitation success, and good neurological outcome following cardiopulmonary resuscitation (CPR) in cardiac arrest patients.Material and Methods: Non-traumatic cardiac arrest patients presenting to the emergency department over a six-month period were included in the study. Blood specimens were collected for SCUBE1 measurement at the start of CPR. SCUBE1 levels investigated at the start of CPR were compared, and their usefulness in predicting patients with long-term survival and exhibiting good neurological prognosis was evaluated.Results: The study group consisted of 65 non-traumatic cardiac arrest patients. Sustained return of spontaneous circulation (ROSC) was achieved in 26 (40%) of these 65 patients, and five (7.7%) cases concluded with good neurological prognosis after three months. Comparison of the patient groups with and without sustained ROSC in terms of SCUBE1 levels investigated at the start of CPR revealed no statistically significant difference between them (p=0.462). However, comparison of the patient groups with good and poor neurological prognosis in terms of SCUBE1 levels at the start of CPR revealed that SCUBE1 levels were twice as high in the poor neurological prognosis group as in the good neurological prognosis group, although the difference was not statistically significant.Conclusion: SCUBE1 levels measured at the start of CPR are not sufficient for predicting post-CPR survival and good neurological outcome.